Effectiveness of Interventions to Improve Preceptor Performance in Nursing Student Competencies - Ummi Kulsum; Rizki Fitryasari; Nuzul Qur’aniati (Indonesian Journal of Global Health Research, 2025)
Perceptors need to be proficient in clinical teaching and assessment in reaching learning objectives while handling client caseload and delivering safe and efficient care. However, evidence to inform best practices for mentor development is limited, as is evidence regarding the efficacy of programs for the mentor role. This study aims to analyse interventions to improve preceptor performance on nursing student competencies. Methods: This study employs a systematic review, with study literature gathered from multiple electronic databases, including Pubmed, Science Direct, ProQuest, and SAGE using a PRISMA flow guidline. Data was collected by searching for research for 2019-2024 and searches were conducted until March 4, 2024. The keywords used are "Intervention" "Improve" "Preceptor" "Student Nursing Performance". Eligible studies require the use of quasi-experiments to identify interventions to improve preceptor performance in the competence of nursing students in different data base sources. Results: A total of 12 articles were analyzed because they provide information about interventions to improve preceptor performance in the competence of nursing students. Five articles on Randomized Controlled Trials, 7 articles using Quasi-experimental design. This article recommends an intervention clinical teaching on One Minute Preceptor because it is effective and can be used in a limited time. Conclusions: Overall, research shows that nursing education should improve recent graduates' readiness to achieve competence. Nurse educators should facilitate comprehensive assistance in order to enable students to acclimatise to the nursing profession’s culture before beginning their clinical education.